China Economic Update, December 2021 : Rebalancing Act - From Recovery to High-Quality Growth - World Bank (World Bank, Washington, DC, 2022)
Following a strong rebound in the first half of 2021, economic activity cooled rapidly in the latter half of the year. The slowdown was partly policy induced, reflecting significant fiscal tightening and regulatory curbs on the financial and real estate sectors, while recurring COVID-19 outbreaks complicated the normalization of contact service activities. This led to a sharp slowdown in investment and sluggish recovery of private consumption, which was only partially offset by stronger-than-expected exports on the back of robust external demand. In addition, power shortages and production cuts aimed at reducing CO2 emissions, which surged in the first half of 2021, also weighed on economic activity.